Fisheries practices and fish diversity in Muda and Beris Lakes: a preliminary survey study - M. Sharifudin,; Zati Sharip, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Beris and Muda are two artificial lakes that have shifted from lotic to lentic system. Despite both lakes were created for irrigation and source of drinking water, they provide fish habitat for human consumption. This study was carried out to find out the effect of different management approaches on fish in the studied lakes. Muda Lake was utilized for commercial fisheries; this lake hosts around 50 active fishermen compared to Beris that has all part-time fishermen. The catch and the existence of fish landing centre makes the Muda a successful lake for commercial fisheries. In contrast, Beris Lake has also developed its fisheries activity, but concentrates more on the recreational aspect which is well developed at this lake. The existence of many chalets providing boats for sport fishing makes Beris Lake more successful than Muda Lake. The study found a contrasting impact of introducing different alien species where may cause benefit at Muda Lake such as increasing fish stocks of Tilapia (Orechromis spp.) but developed problems in Beris Lake when Toman (Channa micropeltes) was introduced to this lake which reduced the number of native fish species compared to previous studies. This study finds that different methods of fishery management and the introduction of alien species may affect the fisheries activities and fish diversity in those lakes.